2022
DOI: 10.3390/ma15145079
|View full text |Cite
|
Sign up to set email alerts
|

Bending Strength of Polyamide-Based Composites Obtained during the Fused Filament Fabrication (FFF) Process

Abstract: The research shows the comparison between two types of polyamide-based (PA) composites and pure, base material. The conducted analysis describes how the additions of carbon fibers and glass microbeads affect the material’s properties and its behavior during the bending tests. All samples have been tested in the three main directions available during the FFF process. To extend the scope of the research, additional digital-image-correlation tests and fracture analyses were made. The obtained results indicated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…A range of variability was demonstrated after a decrease in density, what shows that a Menger sponge with a hexagonal cavity would have the lowest normalized thermal and electrical conductivity as the effective density decreased and an increase in the order of the fractal leads to a near-zero Poisson's ratio [8]. A large number of articles base their research on the generation of beams, which are then subjected to bending tests that make it possible to determine a wide range of coefficients and variables relevant to the selection of the appropriate material or infill pattern [9,10]. From a fractal point of view, however, the infinite possibility of generating cells should be constantly emphasized [11,12].…”
Section: Badanie Struktur Komórkowych Zbudowanych Z Modeli Samopodobn...mentioning
confidence: 99%
“…A range of variability was demonstrated after a decrease in density, what shows that a Menger sponge with a hexagonal cavity would have the lowest normalized thermal and electrical conductivity as the effective density decreased and an increase in the order of the fractal leads to a near-zero Poisson's ratio [8]. A large number of articles base their research on the generation of beams, which are then subjected to bending tests that make it possible to determine a wide range of coefficients and variables relevant to the selection of the appropriate material or infill pattern [9,10]. From a fractal point of view, however, the infinite possibility of generating cells should be constantly emphasized [11,12].…”
Section: Badanie Struktur Komórkowych Zbudowanych Z Modeli Samopodobn...mentioning
confidence: 99%
“…In the following article, four orders of hierarchical structures based on the Menger cube were investigated and subjected to mechanical, electrical and thermal tests, where a range of variability was demonstrated after a decrease in density, and it was shown that a Menger sponge with a hexagonal cavity would have the lowest normalized thermal and electrical conductivity as the effective density decreased and an increase in the order of the fractal leads to a near-zero Poisson's ratio [15]. A large number of articles base their research on the generation of beams, which are then subjected to bending tests that make it possible to determine a wide range of coefficients and variables relevant to the selection of the appropriate material or infill pattern [16,17]. From a fractal point of view, however, the infinite possibility of generating cells should be constantly emphasized [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…A significant advantage of polyamides is their ability to combine with other materials, which opens up possibilities for creating composites with enhanced mechanical properties [ 33 , 34 , 35 ]. For example, the addition of glass or carbon fibers to a polyamide matrix can significantly increase the stiffness and tensile strength of the components produced [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%